The emperor's new groove [videorecording (DVD)]. - Spade, David; Kitt, Eartha; Warburton, Patrick; Goodman, John (Disney, 2000)
Arrogant Emperor Kuzco is turned into a llama by his devious advisor, Yzma, and her hunky henchman, Kronk, who want to rid the kingdom of this beast of burden. Now the ruler who once had it all must form an unlikely alliance with a pleasant peasant named Pacha. Together, Kuzco and Pacha must overcome their differences, as they embark on a hilarious adventure. Includes never-before-seen footage and a sneek peak at Kronk's New Groove.